Avaliação da eficiência técnica dos hospitais da Rede São Camilo - Silva, Francisco Gomes da (2009)
Has the objective to value the technique efficiency of twenty-five hospitals joined to SUS (Sistema Único de Saúde) Health system unique, run by São Camilo charity society, a private organization without making a profit. The researched departments locate in the five regions of the country: North, Northeast, South, South-east, and Center-west and in 11 states. The collected informations will be analyzed in retrospective series of three years (2006 to 2008) using DEA (Data Envelopment Analisis) , advised by the products and constant returns of scale, having intention of getting results towards to the best productivity and to keep the same level in the efficiency of enforcement of included. We can say the results are good to show the efficiency technique of the charity society São Camilo Hospitals, showing that some hospital can be used as benchmark by others, as well as the inefficient hospitals should have used these techniques to be come efficient.